2012
DOI: 10.1016/j.msea.2012.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Work-hardening behaviors of magnesium alloy sheet during in-plane cyclic loading

Abstract: This paper presents the work-hardening behaviors of a rolled AZ31B magnesium alloy sheet during in-plane cyclic loading. The overall trend of the stress-strain curve was as follows. As established before, the yield stress under compression was considerably less than that under tension, and an inflected shape was observed in the stress-strain curve during the subsequent tension. Furthermore, an asymmetric evolution of work-hardening was observed as follows. The rate of work-hardening in the late stage of compre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 66 publications
(54 citation statements)
references
References 40 publications
(61 reference statements)
2
48
0
Order By: Relevance
“…These authors reported that the cyclic hardening/softening behavior varied as the strain amplitudes and cycles changed. Similar results [20][21][22][23] were observed for Mg alloys, which have the same hcp crystal structure as Ti. Plane-strain compression tests were performed by Ayman et al [14].…”
Section: Introductionsupporting
confidence: 80%
See 4 more Smart Citations
“…These authors reported that the cyclic hardening/softening behavior varied as the strain amplitudes and cycles changed. Similar results [20][21][22][23] were observed for Mg alloys, which have the same hcp crystal structure as Ti. Plane-strain compression tests were performed by Ayman et al [14].…”
Section: Introductionsupporting
confidence: 80%
“…This mechanism may be explained in terms of an analogy with Mg alloy sheets as follows. It was reported that in a Mg alloy sheet, a retardation of the beginning of the second rapid increase in work-hardening, i.e., the expansion of plateau region, was observed during compression in cyclic loading [21,35]. This work-hardening behavior occurred for the following reason.…”
Section: Cyclic Loadingmentioning
confidence: 94%
See 3 more Smart Citations